Thermal Performance and Durability of Materials on Concrete-Wood Floor Coverings - Eugene Pradipto; Abdul Robbi Maghzaya (Journal of Architectural Research and Design Studies, 2020)
Floor coverings have an important role in buildings. Apart from being the basis for activities in the building, floor coverings also play a role in maintaining room and surface humidity due to the influence of soil and environmental humidity and maintaining room temperature or floor surfaces to be comfortable to use. This function becomes more vital, especially in buildings in a climate where the temperature difference between day and night is large, resulting in very hot days and very cold nights. The problem raised in this study is to offer a floor covering model that can provide a comfortable temperature on the floor surface which results in a quality performance that can keep the surface temperature close to neutral. In this study, observed and tested the temperature and durability of concrete floor blocks with wood branch waste. The construction of this concrete-wooden floor block uses local materials that are easily available and worked on by the common people. The wood elements have the potential to maintain temperature stability in changing environmental temperatures.Keywords: thermal Insulator, wood floor, concrete floor